Pencegahan Perilaku Bullying dan Dampaknya melalui Sahabat Anti Bully di SDN 08 Tanjung Lago - Rizki Amaliyah; Athiyah Zalfa Riswanda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The Prevention of Bullying Behavior and Its Impacts Through the Anti-Bullying Peer Program at SDN 08 Tanjung Lago” is based on the need not only to increase students’ knowledge about bullying, but also to establish a peer support network that provides mutual reinforcement. The methods employed involve an integrated learning approach that is simple, interactive, and participatory, including communicative material presentation, small-group discussions, experiential learning, observation, and evaluation through pre-tests and post-tests.The results of this community service program demonstrate that the intervention was effective in improving students’ understanding and changing their behavior related to bullying. Through psychoeducation and group counseling, students became more aware of the forms and impacts of bullying, and showed improvements in empathy, emotional regulation, and assertive communication skills.